Learning Strategies for Equal Education Programs for Learning Citizen in Non-Formal Education - Pahenra A Nongko; Hasmira Said; Yaman La Ndibo; Ridwan Yusuf Deluma; Parida Parida (International Journal of Research in Education, 2024)
Equal education programs in non-formal education units are an important means of ensuring access to education for students who have been marginalized from formal education. In facing complex challenges such as the inability to access formal education for various reasons, learning strategies are key in achieving educational equality. This research aims to explore various effective learning strategies in the context of equality education in non-formal education units. This type of research uses a descriptive qualitative approach, namely exploring social phenomena through observation, in-depth interviews, and text analysis to understand in depth how these learning strategies are implemented and integrated in non-formal learning environments.. The research results show that effective learning strategies include creating an inclusive learning environment that pays attention to individual needs, providing a curriculum that is relevant and appropriate to the needs of participants, as well as utilizing technology and innovative learning methods consider specific characteristics of equity education, such as experiential learning approaches, distance learning, or technology-based learning. The implication of this research is the importance of developing learning strategies that are adaptive and responsive to the needs of students in equal education in non-formal education units, thereby ensuring that all individuals have equal opportunities to access education and improve their quality of life.